2016
DOI: 10.5194/nhess-16-737-2016
|View full text |Cite
|
Sign up to set email alerts
|

Boulder accumulations related to extreme wave events on the eastern coast of Malta

Abstract: Abstract. The accumulation of large boulders related to waves generated by either tsunamis or extreme storm events have been observed in different areas of the Mediterranean Sea. Along the eastern low-lying rocky coasts of Malta, five sites with large boulder deposits have been investigated, measured and mapped. These boulders have been detached and moved from the nearshore and the lowest parts of the coast by sea wave action. In the Sicily-Malta channel, heavy storms are common and originate from the NE and N… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
56
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(60 citation statements)
references
References 68 publications
4
56
0
Order By: Relevance
“…The methodology can also be utilised with emerging technologies, such as UAV monitoring (Pérez-Alberti and Trenhaile, 2015aTrenhaile, , 2015bBiolchi et al, 2016) to provide greater spatial resolution on the mechanisms that facilitate the transport of intertidal boulders. Furthermore, deployment in coastal revetment blocks could help mitigate against damage or loss to coastal defence engineering works.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The methodology can also be utilised with emerging technologies, such as UAV monitoring (Pérez-Alberti and Trenhaile, 2015aTrenhaile, , 2015bBiolchi et al, 2016) to provide greater spatial resolution on the mechanisms that facilitate the transport of intertidal boulders. Furthermore, deployment in coastal revetment blocks could help mitigate against damage or loss to coastal defence engineering works.…”
Section: Resultsmentioning
confidence: 99%
“…It is well documented that storm waves have the ability to detach, transport and deposit boulders on intertidal shore platforms (Barbano et al, 2010;Etienne and Paris, 2010;Paris et al, 2011;Shah-hosseini et al, 2011;Stephenson and Naylor, 2011;Cox et al, 2012;Biolchi et al, 2016). Boulder accumulations on shore platforms frequently develop distinctive geomorphic features such as clusters, ridges, fields and cliff top deposits (Nott, 2003a;Paris et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Other coastal features, such as tidal notches, sea stacks, arches and caves occur mainly along the western coast (Biolchi et al, 2016b). Along the eastern coast of Malta and Comino, large boulder deposits ascribed to extreme wave events have been described by Biolchi et al (2016a) and Farres (2014, 2015). Furlani et al (2013) and Lambeck et al (2011) reported that sea level was 130 m lower than the present day during the LGM and that the Maltese archipelago has been tectonically stable since the Last Interglacial.…”
Section: Coastal Landformsmentioning
confidence: 99%
“…In the last decades numerous works have focused on the deposition by extreme marine events of very large boulders in coastal areas Costa et al, 2008Costa et al, , 2011Barbano et al, 2010;Richmond et al, 2011;Biolchi et al, 2016;Dewey & Ryan, 2017;among others). Most of these studies emphasize the great difficulty in distinguishing boulder fields deposited by storms from those originated by tsunamis (Noormets et al, 2004;Dawson et al, 2007;Imamura et al, 2008;Goto et al, 2009Goto et al, , 2010, although until recently it was believed that storm waves were neither capable of moving large boulders nor to achieve this at high altitudes above sea level.…”
Section: Introductionmentioning
confidence: 99%